Biogeochemical behavior and pollution control of arsenic in mining areas: A review - Zhuang, Fan; Huang, Jingyi; Li, Hongguang; Peng, Xing; Xia, Ling; Zhou, Lei; Zhang, Teng; Liu, Zhenghua; He, Qiang; Luo, Feng; Yin, Huaqun; Meng, Delong (Frontiers in Microbiology, 2023)
Arsenic (As) is one of the most toxic metalloids that posses many forms. As is constantly migrating from abandoned mining area to the surrounding environment in both oxidation and reducing conditions, threatening human health and ecological safety. The biogeochemical reaction of As included oxidation, reduction, methylation, demethylation and else, which is closed associated with microbial metabolisms. The study of the geochemical behavior of arsenic in mining areas microbial remediation of arsenic pollution have great potential and are hot spots for prevention and remediation of arsenic pollution. In this paper, we review the distribution and migration of arsenic in the mining area, focus on the geochemical cycle of arsenic under the action of microorganisms and summarize the factors influencing the biogeochemical cycle of arsenic, and strategies of arsenic pollution in mining areas are also discussed. Finally, the problems of the risk control strategies and the future development direction are prospected.